Effect of a Comprehensive Aids Curriculum on a Knowledge and Attitudinal Changes in Northern Canadian College Students - Moskal, Rosemary J. (Canadian Journal of Counselling and Psychotherapy, 2011)
A comprehensive AIDS curriculum was designed to help college students learn the facts about HIV transmission and prevention, discuss personal opinions, clarify values, and develop the skills necessary to practice low risk behaviours. The course was implemented over two months to 123 predominantly aboriginal college students (80%) who were attending the Fort Smith Thebacha Campus of Arctic College in the Northwest Territories. Eight intact classes of students were divided between the control and experimental groups and a questionnaire was administered as the pre-test and post-test instrument. The experimental subjects who received the course, differed significantly from the control group in knowledge of AIDS transmission and prevention and attitude towards low risk behaviours and towards those afflicted with the AIDS virus. The study suggests that AIDS courses designed specifically for various target groups can be successful in obtaining effective educational objectives among college students.